2016
DOI: 10.1097/ijg.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of Bacteria on Bleb Surface After Trabeculectomy With Adjunctive Mitomycin C

Abstract: It is not rare to detect the bacterial organisms on the bleb surface in glaucomatous eyes that had undergone trabeculectomy. The prevalence varied with the season and was highest in the autumn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Because new quinolones are currently the main antibiotic agents used after ophthalmologic surgery, we selected articles with a high level of evidence that covered cases after 2000, when new quinolones were launched, owing to the nature of setting guidelines for the next several years. The only relevant studies were the four reports [243][244][245][246] that analyzed the use of antibiotic agents in 104 eyes with bleb-related infection in a nationwide survey of bleb-related infection conducted by the Japan Glaucoma Society. This study is a prospective, large-scale study of Japanese patients, in which most patients (40 of 42 eyes in the long-term use group) were using new quinolone antibiotics.…”
Section: Strength Of Evidence For Cqmentioning
confidence: 99%
See 1 more Smart Citation
“…Because new quinolones are currently the main antibiotic agents used after ophthalmologic surgery, we selected articles with a high level of evidence that covered cases after 2000, when new quinolones were launched, owing to the nature of setting guidelines for the next several years. The only relevant studies were the four reports [243][244][245][246] that analyzed the use of antibiotic agents in 104 eyes with bleb-related infection in a nationwide survey of bleb-related infection conducted by the Japan Glaucoma Society. This study is a prospective, large-scale study of Japanese patients, in which most patients (40 of 42 eyes in the long-term use group) were using new quinolone antibiotics.…”
Section: Strength Of Evidence For Cqmentioning
confidence: 99%
“…Long-term use of antibiotics may lead to changes in the conjunctival microflora and the appearance of resistant bacteria. In a study of resistant strains toward new quinolone antibiotic agents on the surface of filtration bleb after trabeculectomy, there was no significant difference in culture positivity between eyes with and without long-term antibiotic use [245]. In 26 eyes with long-term use of new quinolone antibiotics, resistant bacteria were found in nine eyes, of which six were Staphylococcus epidermidis [246], which makes endophthalmitis less likely to become severe.…”
Section: Strength Of Evidence For Cqmentioning
confidence: 99%
“…The association with gender is not clearly proven. Seasonal variation in temperature and humidity may influence the conjunctival flora and therefore, the rate of BRI [53].…”
Section: Risk Factorsmentioning
confidence: 99%
“…When trying to determine the effect that glaucoma has on the VR-QOL, the VFQ-25 is frequently used to track the outcome. Previous studies that examined the VFQ-25 reported it to be useful, sensitive, and specific when investigating relationships between the VF disturbance due to glaucoma and the QOL in glaucoma patients [49]. …”
Section: Introductionmentioning
confidence: 99%